Cultural knowledge of non-Muslim nurses working in Saudi Arabian obstetric units - E. M. Sidumo; V. J. Ehlers; S. P. Hattingh (AOSIS, 2010)
Culture defines how persons behave towards each other. When nurses and patients belong to different cultures, culture-based misunderstandings could influence the nurse-patient relationships and interactions adversely. The purpose of the study was to determine non-Muslim nurses' knowledge about Muslim traditions pertaining to obstetric units in a Muslim country. A quantitative descriptive research design was adopted. The population comprised 67 nurses, but the accessible population consisted of 52 nurses who were working in the participating hospital's gynaecological wards during the data collection phase. However, only 50 nurses completed questionnaires as two nurses did not want to participate in the study. The Statistical Package for the Social Sciences (SPSS Version 11.5) was used to analyse the data. The research results indicate that non-Muslim nurses lacked knowledge about Muslim practices concerning breastfeeding, Ko'hl, the "evil eye", modesty, medicine and food taboos. If these aspects could be addressed during the recruitment and inservice education of non-Muslim nurses working in Muslim countries, this could enhance the quality of culture-competent nursing care.